(untitled) (The Pakistan Development Review, 2000)
Mr President, Distinguished Delegates, Excellencies, Colleagues, Ladies and Gentlemen: Assalam-o-Alaikum. The Annual Conference of the Pakistan Society of Development Economists has traditionally provided the people of Pakistan—both practising economists and ordinary citizens—with a forum to debate in a rigorous analytical framework the major economic issues facing the country. In this context, the theme of the current conference “Growth, Poverty and Decentralisation” is particularly appropriate as Pakistan begins the 21st century. Many important issues will be discussed by the honourable participants during the Conference and an excellent start reflecting the quality of the debate has been made by the paper just presented by Dr Kemal. I, on my part, would like to take this opportunity to talk about Pakistan’s economy in an overall poverty elimination perspective and particularly the potential and challenges facing it in this regard. As a starting point, a summary of the potential of the Pakistan economy is in order. First, Pakistan is the home of the oldest and largest integrated land and water systems in the world. The world’s other old river basins—the Nile and the Tigris/Euphrates—have remained relatively minor, while Pakistan’s Indus Basin is still vital and robust. Last year, Pakistan’s record wheat crop again showed the world the potential of the Great Indus Food Machine.